(untitled) (Bangladesh Journal of Agriculture, 2023)
The present research spans two consecutive growing seasons (2021-22 and 2022-23) at the Spices Research Centre, Shibganj, Bogura to evaluate the growth and yield attributes of the betel vine genotypes. The inaugural season (2021-22) focused solely on line BL0027, while the following season (2022-23) included multiple betel vine lines, BL0025, BL0027, BL0028, BL0030, and BL0040, with BARI Pan-3 as check variety. Experimental plots were arranged in a Randomized Complete Block Design (RCBD) with three replications. Data were collected three times throughout the leaf harvesting period, encompassed fifteen morphological traits. The results highlight significant genotypic variations in vine growth, morphology, and yield characteristics. During season 1 (2021-22), genotypes exhibited varying vine lengths, daily growth rates, internode dimensions, and leaf traits, underscoring genetic diversity. BL0027 consistently displayed superior growth and yield attributes, and closely followed by BARI Pan-3 in the season 2 broad assessments. However, genotypic variations persisted, emphasizing the influence of genetics on betel vine attributes. These findings are crucial for betel vine breeding programs and agricultural practices, offering insights into genetic diversity and potential for tailored cultivation. Future research should explore the genetic and environmental factors underlying these traits to optimize betel vine cultivation and management. Bangladesh J. Agri. 2023, 48(2): 86-93